Creation of Structural Polymer Composite Materials for Functional Application Using Physicochemical Modification. (26th August 2019) - Kolosov, Aleksandr E.; Sivetskii, Volodymyr I.; Kolosova, Elena P.; Vanin, Volodymyr V.; Gondlyakh, Aleksandr V.; Sidorov, Dmytro E.; Ivitskiy, Igor I.
Abstract : The various aspects of physicochemical modification of the components of structural materials of functional application based on classical composites and nanocomposites are analyzed. Potential applications of such materials are briefly described. Ultrasonic cavitation treatment is considered as a basic method of physical modification when obtaining the indicated classes of composites. The influence of ultrasonic treatment modes on the technological and operational properties of reactoplastic polymers, as well as on the hardening of reinforced composites based on them, is investigated. Technical means of ultrasonic cavitation processing of liquid binders and polymer composites based on them are briefly described. An effective spectrum of interrelated structural and technological parameters of ultrasonic treatment has been characterized, which is established by calculation and experimentally-statistically. The design issues of the technological processes of obtaining polymer composites of functional application are analyzed. The efficiency of creating carbon fiber composite materials, as well as the prospects for creating of these materials based on reinforcing fabric with nanomodified fillers, is described. The methods of obtaining functional nanomodified carbon-composites with improved physicomechanical and operational properties, in particular with increased strength and electrical conductivity, are characterized. The effectiveness of the ultrasonic treatment and production of nanomodified thermoplastic composite materials by extrusion method is considered. Some issues of forming products from intelligent polymer composites are analyzed. The results of the survey can be used in the design of advanced technologies for the creation of functional polymer composites of functional application.